ALGORITMA GENETIKA PADA PENYELESAIAN AKAR PERSAMAAN SEBUAH FUNGSI - Akhmad Yusuf; Oni Soesanto (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2012)
The Genetic Algorithm is one approach to determining global optimum that is based on the theory of evolution. Outline the steps in this procedure starting with establishing a set of potential solutions and making changes with some iterations with genetic algorithms to get the best solution. Calculation the root of a function is actually a classic problem in mathematics. For that, various methods have been numerically developed. From the results of the implementation of genetic algorithm to find the root of the equation of a function h (x1, x2) = 1000 (x1-2x2) 2+ (1-x1) 2 in can be that FitMax (genome 9) = 10, FitMin (genome 107) = 0, FitAvr = 0.153, FitTot = 30.6, Best Genome: 10011001001000110010, x1 = 1 and x2 = 0.5 and this is the same as the exact value or value actually from the root of the equation